CLOZAPINE ON PARANOID SCHIZOPHRENIA WITH OBESITY: A CASE REPORT - Dewa Nyoman Krisna Arijaya (Universitas Udayana, 2014)
Treatments of schizophrenia using atypical antipsychotics provide remission of symptoms and side effects differ between individuals. The use of the method by findingthe right medication often has an impact on patient adherence to treatment. In the caseof a female patient aged 26 years was diagnosed with paranoid schizophrenia andclozapine treatment using 2x25 mg for 6 months. Schizophrenic symptoms hadsubsided and the patient can work, but the treatment was stopped by the parents.Treatment was discontinued because of patient body weight increased to 80 kg frominitial weight 65 kg. Clozapine increases the weight by several mechanisms. Geneticand environmental influences susceptibility to gain weight. Weight gain can also causea large enough increase in obesity-related comorbidities and health risks such as type IIdiabetes mellitus, hypertension, hear t disease and cancer. Subsequent treatment bechanged using atypical antipsychotics risperidone at a dose equivalent. Given alsoeducate and maintain compliance with treatment.